GAMBARAN POLA KONSUMSI PANGAN DAN POLA PENYAKIT PADA USIA LANJUT DI WILAYAH KERJA PUSKESMAS TAPAKTUAN KECAMATAN TAPAKTUAN KABUPATEN ACEH SELATAN TAHUN 2012 - Nova Elvia; Muhammad Arifin Siregar; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Everybody wants to have long, useful, and happy life. To life a healthy life in our old days needs a supply of good and nutritious food which is balanced with the elderly’s physiological condition. The objective the study is to find out the description of the food consumption and disease pattern among elderly in the working area of Health Center Tapaktuan, Tapaktuan Subdistrict, Aceh Selatan District in 2012. This is a descriptive study with crosssectional design. The population of this study was 638 person of  ≥ 60 years of age, and 85 of them were selected to be the samples for this study through systematic random sampling technique. The data of the food consumption pattern were obtained through questionnaire distribution and food frequency form, while the data for disease pattern were obtained by looking at the kind of disease and the length of being sick. The result of this study showed that most of the kinds of food consumed by the elderly was in the inadequate category 55,3%, the texture of the food was in the improper category 61,2%, and the eating frequency of the elderly disorganized. Based on the pattern of disease they experienced, in general the elderly has suffered from degenerative disease such as hypertension, rheumatism, diabetes mellitus, heart disease, osteoporosis, and stroke with the length of being sick of > 2 weeks 47,1%.   Keywords: Alpha Food Consumption Pattern, Disease pattern, Elderly